Developing sustainability learning in business school curricula – productive boundary objects and participatory processes. Issue 2 (1st February 2020) - Edwards, Melissa; Brown, Paul; Benn, Suzanne; Bajada, Christopher; Perey, Robert; Cotton, Deborah; Jarvis, Walter; Menzies, Gordon; McGregor, Ian; Waite, Katrina
Abstract: Sustainability learning is holistic and complex as it draws on diverse disciplines and can be interpreted differently within individual pedagogies. Embedding sustainability across and within business schools relies on developing suitable boundary objects. These may include representations such as models, frameworks or classificatory schemes that are malleable enough to be adapted for use within the disparate disciplines and pedagogies, yet durable enough to be recognisable and to maintain consistency across them. Boundary objects thus allow the sharing of ways of knowing or practice across various social boundaries. This paper outlines how participatory curriculum development processes can enable sustainability to be embedded in a business school curriculum. Distinct phases of the process were marked by different ways of knowing, as disciplinary-specific academics developed and embedded sustainability into and across curricula. Boundary objects were both outcomes and productive facilitators of this process. They acted as catalysts and attracted ongoing processes of dialogue, debate and meaning-making between these academics. The institutional context provided enabling conditions to legitimize outcomes from the participatory process. The process may be replicable in other business schools by the use of boundary objects.